Efeito dos sistemas de criação semi-intensivo (viveiro escavado) e intensivo (tanque-rede) no desenvolvimento produtivo do pintado, Pseudoplatystoma corruscans (Spix & Agassiz, 1829) (Siluriformes: Pimelodidae) - Sousa, Andressa Daniela Liranço de [UNESP] (2005)
The pintado, Pseudoplatytoma corpsman (SPIX & AGASSrz, 1829) (Siluriforms: Pimelodidae) presents the taste of its meat which is appreciated in the Brazilian market and its cultive is an alternative of investment from aquaculture and industry in the country. It is also species appreciated in recreational fishing. This experiment was carried out in the Polo Regional de Desenvolvimento Sustentável do Vale do Ribeira, DDD, APTA, in Pariquera-Açu, São Paulo, Brazil, with the objective to verify the effect of systems semi-intensive (earthen ponds, P) and intensive (cages, C), with the same number of fish. Weight and length gain., condition factor (K), daily weight gain (DWG), feed conversion apparent (AFC), feed consumption (FC) and survival (S) were evaluated. Of a total of three hundred (300) one-year-old fish, one hundred fifty (150) were stocked in 01 pond (P) (600m2) and one hundred fifty (150), distributed in 03 cages (C) (2,0 m3), fifty (50) in each one, from Jan./04 to Jan./05. The fish were fed twice a day, with extruded commercial ration for carnivores with 15.0 mm floating pellets containing 40 % crude protein (CP) and, 3,110 Kcal of digestible energy (DE) per Kg of feed and, adjusted monthly. The water was monitored and the following mean values were obtained: T = 24.08°C; pH = 6.89; O2 D = 7.57 mg/L. The values of mean initial and final length and weight were: Pond (P) = 57.31 ± 6.42 and 74.07+- 4.34 cm; 1.48+-0.46 and 3.41+-0.58 Kg; Cages (C) = 55.05+-4.11 and 70.33+-5.02 cm and 1.27 +- 0.34 a 2.94+- 0,6 kg, respectively. The equations of the relation Wt x Lt were: Wt = 9 xl0-4Lt 3,5008 (P) e Wt = 4 x10-7Lt 3,7509 (C). The mean values of K = 0.009 a 0.036; DWG = 9.29g/day and 8.95g/day; AFC = 3.09 and 4.15; Total ration consume (TRC) = 29.6 g/day and 74,16 g/day, P and C, respectively. Through the variance of analysis can be verified that there are significative interactions of the parameters between ...